On the Existence of Coupled Fractional Jerk Equations with Multi-Point Boundary Conditions - Lei Hu; Yaozhen Han; Shuqin Zhang (Axioms, 2021)
By coincidence degree theory due to Mawhin, some sufficient conditions for the existence of solution for a class of coupled jerk equations with multi-point conditions are established. The new existence results have not yet been reported before. Novel coupled fractional jerk equations with resonant boundary value conditions are discussed in detail for the first time. Our work is interesting and complements known results.